Novel multifunctional dexamethasone carbon dots synthesized using the one-pot green method for anti-inflammatory, osteogenesis, and osteoimmunomodulatory in bone regeneration. (22nd September 2022) - Wan, Chang; Hu, Mengyue; Peng, Xu; Lei, Ningning; Ding, Hongmei; Luo, Yihao; Yu, Xixun
Abstract : Carbon dots with anti-inflammatory, osteogenesis and osteoimmunomodulatory abilities for bone regeneration. Abstract : Bone tissue regeneration is still a major orthopedic challenge. The process of bone regeneration is often disrupted by inflammation. Elevated levels of reactive oxygen species (ROS) can lead to aggravated inflammation and even hinder tissue repairs. Therefore, inhibiting the inflammatory response during the process of bone regeneration and promoting bone tissue regeneration under inflammatory conditions are the goals that need to be achieved urgently. In this work, dexamethasone carbon dots (DCDs) were developed by a one-pot facile hydrothermal method using citric acid, ammonium fluoride, and a trace amount of dexamethasone. The obtained DCDs exhibited good biocompatibility and could promote the differentiation of rBMSCs under both normal and inflammatory conditions. Owing to the abundant-reducing groups, DCDs could also scavenge ROS (˙OH) and retain the pharmacological activity of dexamethasone, thereby reducing the inflammatory response. Moreover, DCDs presented a good osteoimmunomodulatory activity to induce a bone immune microenvironment and further promote the differentiation of BMSCs. DCDs could promote macrophage phenotype switching (from M1-type macrophages to M2-type macrophages) under inflammatory conditions, which was beneficial to the anti-inflammatory response. All in all, DCDs could reduce the inflammatory response of bone tissue and accelerate bone regeneration in combination with the regulation of the bone immune. Undoubtedly, it also provided a new idea for developing a novel carbon nanomaterial for repairing bone tissue defects.